Recent Developments in the Meyer‐Schuster Rearrangement - Justaud, Frédéric; Hachem, Ali; Grée, René (European journal of organic chemistry, 2021)
The Meyer‐Schuster rearrangement is an efficient method to prepare α,β‐unsatured carbonyl compounds starting from propargylic alcohols and this review presents the remarkable progress made during the last decade in this reaction. New efficient catalytic systems have been discovered and many elegant applications have been reported for this rearrangement. To be noticed in particular are the new and efficient cascade processes affording a wide range of carbo‐ and heterocyclic molecules. Moreover, brilliant applications of this rearrangement have been described as well, in the total synthesis of complex natural products and their analogues. Finally, the first examples of aza‐Meyer‐Schuster rearrangements have been recently described as well. A century after its discovery, the Meyer‐Schuster rearrangement appears as a very useful method to prepare α,β‐unsaturated carbonyl derivatives. This comprehensive review highlights the progress of this reaction during the last decade focusing on the new catalysts, the novel cascade reactions, the brilliant applications in total synthesis of natural products, and the first examples of aza‐Meyer‐Schuster rearrangement.